Mujeres en movimiento: geografías negras y movilidades femeninas en el Nuevo Reino de Granada a fines del periodo colonial - Katherine Bonil Gómez (Nuevo mundo - Mundos Nuevos, 2025)
In this article, I analyze the life narratives of two enslaved women and one free woman, constructed in collaboration with legal mediators, focusing on their movements through the geographies of the Magdalena River at the end of the 18th century. At different points in their lives, these women were either forced or chose to move along these geographies in order to escape punishment, flee mistreatment, keep their families together, recover lost property, and seek justice. These narratives highlight the mobility practices that both enslaved and free women forged for themselves, challenging the enslaving structures of control and the Christian discourses that framed the virtuous woman as one who is still, restrained in her body, and confined to the domestic sphere. I analyze these dynamics with two main goals: on the one hand, to make visible the long history of Black female mobility in Colombia, and on the other, to offer points for reflection on studies of mobility, race, gender, and Black geographies, produced from the historical and geographical particularities of Colombia and Latin America.